Evaluation of Microencapsulation Techniques for MICP Bacterial Spores Applied in Self-Healing Concrete - Pungrasmi, Wiboonluk; Intarasoontron, Jirapa; Jongvivatsakul, Pitcha; Likitlersuang, Suched (Scientific reports, 2019)
Concrete cracks must be repaired promptly in order to prevent structural damage and to prolong the structural life of the building (or other such construction). Biological self-healing concrete is a recent alternative technology involving the biochemical reaction of microbial induced calcium carbonate precipitation (MICP). This study determined the most appropriate technique to encapsulate spores of Bacillus sphaericus LMG 22257 with sodium alginate so as to protect the bacterial spores during the concrete mixing and hardening period. Three techniques (extrusion, spray drying and freeze drying) to encapsulate the bacterial spores with sodium alginate were evaluated. The freeze-drying process provided the highest bacterial spore survival rate (100%), while the extruded and spray-dried processes had a lower spore survival rate of 93.8% and 79.9%, respectively. To investigate the viability of microencapsulated spores after being mixed with mortar, the decomposed urea analysis was conducted. The results revealed that the freeze-dried spores also showed the highest level of urea decomposition (metabolic activity assay used as a surrogate marker of spore germination and vegetative cell viability). Thus, the self-healing performance of concrete mixed with freeze-dried spores was evaluated. The results showed that the crack healing ratio observed from the mortar specimens with freeze-dried microencapsulated spores were significantly higher than those without bacteria. This study revealed that freeze drying has a high potential as a microencapsulation technique for application to self-healing concrete technology.